Notes on the Characters of the Cranium found in a Short Cist near Dunse, July 1863 (Proceedings of the Society of Antiquaries of Scotland, 1865)
William Turner provides a report on fragments of a skull found in a short cist in Dunse (see ‘Meeting notes’ Donor (3), p.240). The article includes the cranium’s measurements and speculation on the person’s sex and age at death. The brachycephaly of this and other bones excavated in the UK and Europe are also discussed by the author.